Days spent at home in the last 6 months of life: a quality indicator of end of life care in patients with hematologic malignancies. Issue 1 (2nd January 2020) - Cheung, Matthew C.; Croxford, Ruth; Earle, Craig C.; Singh, Simron
Abstract: Despite advances in the management of hematologic malignancies, a significant proportion of patients die of their disease. We used administrative databases in Ontario, Canada (between 2005 and 2013) to determine the number of days spent at home in the last 6 months of life. We studied the predictors of the median number of days at home (DAH) using quantile regression. For the 11, 127 patients with hematologic malignancies who died, the median number of DAH in the last 6 months was 156 days. Patients with acute leukemias ( p < .0001), women ( p < .0001), and those requiring transfusions ( p < .0001) spent the fewest DAH. Patients assessed by palliative care prior to their last 6 months were likely to spend more time at home ( p < .0001). Providing additional supports for patients nearing the end of life, including earlier access to palliative care and continued transfusion support, may increase the likelihood that patients can die at home.